The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12902-021-00830-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of tooth loss with morbidity and mortality by diabetes status in older adults: a systematic review

Abstract: Objective This systematic review assesses the association of tooth loss (TL), as the exposure, with morbidity and mortality by diabetes mellitus (DM) status, as the outcome, in older adults. Background Individuals with DM have higher prevalence of severe TL and increased risk of developing morbidities and mortality. No systematic review has evaluated the association between TL with morbidity and mortality by DM status. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 70 publications
(145 reference statements)
1
6
1
Order By: Relevance
“…Even though our study did not find other associations with a lack of functional dentition through the logistical regression of our data, systematic and longitudinal studies related tooth loss with obesity [ 13 , 62 , 63 ], depression [ 64 ] and diabetes [ 14 ]. It is noteworthy that the prevalence of socioeconomic vulnerability, whether measured in net terms (personal or family economic income) or multidimensional (RSH), continues to be a constant in studies that measure the severity of tooth loss.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Even though our study did not find other associations with a lack of functional dentition through the logistical regression of our data, systematic and longitudinal studies related tooth loss with obesity [ 13 , 62 , 63 ], depression [ 64 ] and diabetes [ 14 ]. It is noteworthy that the prevalence of socioeconomic vulnerability, whether measured in net terms (personal or family economic income) or multidimensional (RSH), continues to be a constant in studies that measure the severity of tooth loss.…”
Section: Discussioncontrasting
confidence: 81%
“…Maintaining optimal oral health by preserving a natural, healthy and functional dentition contributes to the survival of older adults [ 9 ], since missing unreplaced teeth has been associated with an increase in the risk of malnutrition, frailty and cardiovascular mortality [ 10 ]. Likewise, an association with the decline in cognitive function, dementia, obesity, diabetes and hypertension has been reported [ 11 , 12 , 13 , 14 , 15 ]. In this sense, the WHO’s Oral Health Program has encouraged national planners to strengthen the implementation of systematic programs aimed at improving healthy aging, oral health and a better quality of life for the elderly [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a two-way relationship between low food intake and oral health problems, such as tooth loss, tooth decay and periodontitis [ 38 ]. Additionally, an unhealthy diet and hyperglycemia also lead to tooth loss, dental caries and periodontal diseases [ 16 , 53 , 54 ]. Low protein and energy intake caused by inadequate food intake directly leads to protein–energy malnutrition (PEM) in older adults [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings support the bi-directional relationship between tooth loss and incident diabetes, and the study found that having fewer than 20 teeth was associated with an incident diagnosis of diabetes over a 4-year follow-up, supporting findings from other studies. [48][49][50] In this study, the oldest age group was at higher risk of tooth loss for any reason, but diabetes was a risk indicator for tooth loss following adjustment for age. The clinical significance of this relationship needs further investigation because, as reported by Haworth and colleagues, the reasons for tooth loss in older adults are difficult to determine.…”
Section: Discussionmentioning
confidence: 52%